New records of Notodontidae Stephens, 1829 (Lepidoptera: Noctuoidea) from India - Mazumder, Arna; Sanyal, Abesh Kumar; Schintlmeister, Alexander; Gayen, Subrata; Chandra, Kailash; Raha, Angshuman (Zootaxa, 2022)
The present study discusses the systematic accounts of ten species of the family Notodontidae recorded here for the first time from India. The species were collected from different parts of Indian Himalaya, the majority being reported from the Dihang-Dibang Biosphere Reserve, Arunachal Pradesh. Among these ten species, we present two new combinations under subfamily Spataliinae, viz. Odnarda leechi comb. nov. and Torona lucida comb. nov. based on the affinities in male genitalia structure with these recently upgraded genera compared to the previously considered expanded concept of Biula and Bireta, respectively. Moreover, three genera under subfamily Notodontinae viz. Himalodontosia, Periphalera and Pseudosomera are newly added to the existing Indian Notodontidae fauna with respective species H. mahendra, P. albicauda and P. noctuiformis yunwu. Another five new records include one species of the subfamily Dudusinae - Tarsolepis taiwana, one species of the subfamily Spataliinae - Ogulina ochrocinerea, and three species of the subfamily Notodontinae - Syntypistis synechochlora, S. witoldi and Ptilodon amplius. Thus, the present study updates the Indian Notodontidae richness to a total of 257 species and 15 subspecies (272 species/subspecies including nominotypical subspecies) under 119 genera. Here, we provide species diagnoses with similar congeners along with habitus, genitalia images, information on the bionomy and distribution map for each of these newly recorded species.